IKLIM KOMUNIKASI ANTARA PIMPINAN DAN KARYAWAN - Suprihatini, Taufik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2007)
As institution, FISIP would not go well only relied on existence of instructor staff (lectures) and students without employees. The position of staff administration as an hardware was strategic enough for processing learn to teach. This research aimed to descripts the communication between head of faculty and employees also the spirit of employees in FISIP Undip. This research population description type with qualitative description method. The research population were all of FISIP Undip employees and the sample technique intake used totally of sampling. Data in field was obtained from interview technique that used questioner. The result of this research was descripts that the head build condusif communication climate with aspiratif communication model in bottom up communication characteristic.